Dorongan Bawah Sadar dan Pengendalian Emosi Menurut Alquran - Mirawati, (Prophetic Guidance and Counseling Journal, 2022)
A person's ability to control his emotions shows that humans are able to maintain self-confidence. humans are also a mirror of one's maturity in dealing with any circumstances and subconscious drives have a role in moving humans to fulfill their own activities controlling emotional forms, the purpose of this writing is to find out emotional impulses based on the Koran and how to overcome them. The research approach used is qualitative with the method of literature review or library research. This research focuses on the study of subconscious drives related to emotions in the Qur'an. Library sources come from the Qur'an and the interpretations of expert tafsir scholars. about and secondary sources, namely writing in books or journals related to discussion variables. The analysis used includes collecting data, content analysis and conclusions. The Qur'an contains emotional drives such as anger, forgiveness, sadness, empathy, love and compassion. In addition, the Qur'an teaches about managing emotions. Abstrak Kemampuan seseorang dalam mengendalikan emosinya menunjukkan bahwa manusia mampu menjaga kepercayaan diri. manusia juga merupakan cermin kedewasaan seseorang dalam menghadapi keadaan apa pun dan dorongan bawah sadar memiliki peran dalam menggerakkan manusia memenuhi aktivitas diri mengendalikan bentuk emosi, tujuan penulisan ini untuk mengetahui dorongan emosi berdasarkan Alquran dan cara mengatasinya. Pendekatan penelitian yang digunakan adalah kualitatif dengan metode kajian literatur atau library research. Penelitian ini berfokus pada kajian dorongan alam bawah sadar terkait emosi dalam Alquran. Sumber Pustaka berasal dari Alquran dan tafsir ulama ahli tafsir. Sumber sekunder yaitu tulisan pada buku atau jurnal terkait variabel pembahasan. Analisis yang digunakan meliputi mengumpulkan data, analisis isi dan kesimpulan. Alquran berisi dorongan emosi seperti marah, memaafkan, kesedihan, empati, cinta dan kasih sayang. Selain itu, Alquran mengajarkan tentang pengelolaan emosi.